New records of two rare genera, Monstrotanais Kudinova-Pasternak, 1981 and Robustochelia Kudinova-Pasternak, 1983 (Tanaidacea: Crustacea) - Jóówiak, Piotr; Błażewicz-Paszkowycz, Magdalena (Zootaxa, 2007)
Two new species of two rare genera, Monstrotanais ingens n. sp. and Robustochelia virilis n. sp., have been described from the material collected during cruises of r/v Eltanin. The type species of Robustochelia, R. robusta (Kudinova-Pasternak, 1970) has been redescribed based on the well preserved holotype. Diagnoses of the two genera have been amended and key for Robustochelia species has been proposed. Currently two species are assigned to Monstrotanais and four to Robustochelia. Robustochelia solida Larsen, 2005 is now excluded from the genus and possibility of establishing a new genus for the species is considered.